Peran Biomekanika dalam Meningkatkan Performa Olahraga dan Mencegah Risiko Cedera pada Atlet - Wahyu Prasetio; Abdul Aziz Hakim (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The primary challenge in modern sports lies in the suboptimal utilization of biomechanics to simultaneously enhance athletic performance and systematically reduce injury risk. This study adopts a non-empirical approach grounded in conceptual analysis and comprehensive literature synthesis to construct a theoretical framework linking biomechanical variables, movement efficiency, and injury potential. The methodology integrates thematic, comparative, and interpretative analyses of contemporary scientific studies to identify causal patterns and conceptual gaps within existing research. The findings indicate that performance efficiency is strongly influenced by the optimization of the kinetic chain and the precise distribution of mechanical loads, while injury risk is closely associated with cumulative biomechanical deviations. Furthermore, the integration of advanced technologies, such as wearable devices and artificial intelligence-based analytics, enhances predictive capabilities in injury detection and improves the accuracy of performance evaluation. The discussion highlights that a data-driven and integrative biomechanical approach enables the development of more adaptive, effective, and sustainable training strategies within the evolving landscape of modern sports science.